Open Repair of Large Hepatic Artery Pseudoaneurysm Without Collateral Circulation: A Case Report - Wen, Xin; Chen, Xiyang; Zhao, Jichun; Luo, Xin; Guo, Qiang; Du, Xiaojiong; Yuan, Ding; Huang, Bin (Frontiers in Surgery, 2022)
Hepatic artery pseudoaneurysm is a rare arterial disease. This case report describes a patient with hepatic artery pseudoaneurysm who presented with recurrent epigastric pain over a 4-month period. Computed tomography angiography (CTA) showed aneurysmal enlargement of the hepatic artery measuring 55 mm × 46 mm. The angiographic information is as follows: (1) the common hepatic artery originated from the superior mesenteric artery; (2) the proper hepatic artery originated from the common hepatic artery; (3) the proper hepatic aneurysmal disease had no collateral circulation. After careful consideration, the patient underwent an open surgical repair (OSR). The patient recovered well without any associated complications. The 1-year follow-up of patients did not reveal any relevant complications. The treatment choice, puzzles, and reflections of this case are all discussed in this article.